The relationship between environmental disclosure and corporate characteristics among Malaysian public listed company / Noor Hashira Eidan - Eidan, Noor Hashira (2011)
The primary of this dissertation is to investigate the relationship between various corporate characteristics with environmental disclosure of the Malaysian Public Listed company. These characteristic include environmental sensitive company, profitability, leverage ratio as well as company either involve with the ISO Certificate or not. This dissertation also examine the current trend of environmental disclosure among Malaysian Public Listed Company. The extent of environmental disclosure items in corporate report is measured using content analysis and the score sheet developed in this study. The result from this study found that only ISO certificates company have a positive significant impact towards environmental disclosure among Malaysian companies. Industry type, profitability and leverage is not an important determinant to the environmental disclosure. The findings in this study contribute to the body of knowledge a new dimension of environmental reporting.